TRIB3-Regulated Akt Signal Pathway Affects Trophoblast Invasion in the Development of Preeclampsia - Sui, Xin; Zhang, Lei; Zhang, Xu-Feng; Zhang, Ya (American Journal of Perinatology, 2021)
Objective The aim of the study is to explore the mechanism of tribbles pseudokinase 3 (TRIB3)-regulated Akt pathway in the development of preeclampsia (PE).Study Design TRIB3 expression in the placenta of PE patient was determined by quantitative reverse transcriptase polymerase chain reaction and western blotting. Then HTR-8/SVneo or JEG-3 cells were transfected and divided into Mock, Control siRNA, TRIB3 siRNA-1, and TRIB3 siRNA-2 groups. Cell proliferation, invasion, and migration were determined by MTT assay, Transwell assay, and wound healing test, while the expression of TRIB3 and Akt pathway was measured by western blotting. PE rats were treated with TRIB3 siRNA, and blood pressure, 24-hour urinary protein, as well as serum levels of sFlt-1 and vascular endothelial growth factor (VEGF) were measured.Results The placenta of PE patients presented with increased TRIB3 expression. In comparison with Mock group, the proliferation, invasion, and migration of HTR-8/SVneo and JEG-3 cells in TRIB3 siRNA-1 group and TRIB3 siRNA-2 group increased, with decreased TRIB3 expression but enhanced expression of p-Akt/Akt, MMP-2, and MMP-9. Rats in PE group showed increases in mean arterial pressure, SBP, 24-hour urinary protein, and serum sFlt-1 levels, but decreases in serum VEGF levels, fetal weight, and placental efficiency. Moreover, TRIB3 expression was upregulated, while p-Akt/Akt was downregulated in the placenta of rats in PE group. However, indicators above were significantly improved in rats treated with TRIB3 siRNA.Conclusion TRIB3 was upregulated in the PE placenta, while silencing TRIB3 activated the Akt signaling pathway to promote the invasion and migration of trophoblast both in vitro and in vivo and ameliorated the development of PE symptoms in the PE rat model.Key Points
Keywords: TRIB3; preeclampsia; trophoblast; Akt signal pathway